Background, Recruitment, and Perceived Factors for Winning: A Qualitative Inquiry into the Perspectives of Local Women Politicians (LWPs) in Northern Mindanao, Philippines - Necosia, Richard Ian Mark (Future Science / FSH-PH Publications, 2024)
Despite being globally acknowledged as one of the more gender-equal societies, the Philippines faces persistent challenges in achieving gender parity, especially in political representation, which necessitates a deeper investigation into women's political participation at the local level. This study delves into the nuanced dynamics of local women politicians (LWPs), examining their political background, recruitment into politics, and perceived factors for electoral success. Utilizing a phenomenological research design, the study aims to articulate and comprehend the essence of LWPs' lived experiences. Grounded in Interpretative Phenomenological Analysis (IPA), the methodological framework facilitates a nuanced understanding of individual and societal realms. Six LWPs from Bukidnon, Northern Mindanao, participated in the study to comprehensively explore commonalities and distinctions in their political experiences. The findings revealed five themes of LWPs' political background: apolitical origins, entry into politics during young adulthood, involvement in philanthropy, membership in political families, and substantial political experience. The political recruitment of LWPs is revealed through the support of the church and the influence of political families. Additionally, LWPs' perceived factors for winning in electoral politics encompass three key themes: membership in a political family, philanthropic endeavors, and the prevalence of money politics. The lived experiences of LWPs resonate with prior research on